Hubungan Di Antara Sikap Terhadap Sains Dan Pencapaian Di Dalam Matapelajaran Sains Di Kalangan Pelajar-Pelajar Tingkatan 4 - Mior Shaharuddin, Mior Abu bakar (2002)

(untitled)
The main purpose of the study is to determine the relationship between attitude towards science and student achievement in science. The research involved the analysis of 23 item questionaire completed by 212 form four students. 4 schools in Pulau Pinang were studied in the research. From the research the level of attitude towards science among 212 form four students is determined. This research also enable the comparison made toward attitude towards science based on gender, school streams and school categories. All quantitative data were analyzed using SPSS software. Result of the study demonstrate a positive correlation between attitude towards science and achievement in science. It was shown that overall both boys and girls have positive attitude toward science. Research also indicated that attitude towards science differing based on school streams and schools categories but not on gender.